PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA INTERAKTIF BERBASIS KETERAMPILAN ABAD 21 PADA MATERI ARITMATIKA SOSIAL - Ramadhani, Zahrotul Luthfina; Napfiah, Siti (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2022)
Research on the development of interactive mathematics learning media based on 21st century skills, namely using the google sites application on social arithmetic material aims to: 1) Produce interactive mathematics learning media on Social Arithmetic concepts that are suitable for use 2) Find out how the results of developing 21st century skills-based interactive mathematics learning media in the form of a google sites application. This research is a type of development research using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The sample of this research is the seventh grade students of MTs Sunan Bonang Pujon, Malang. The data collection process uses an instrument in the form of a validation sheet with the aim of measuring the validity of the Google Sites Learning Media, a test to determine student learning outcomes and student responses to the Google Sites Learning Media which was developed to determine the effectiveness of Google Sites. The results of the material expert test obtained a score of 90% which showed valid criteria and the results of the media expert test obtained a score of 90% which showed valid criteria. Student test results obtained an average value of 82,5 where the value has met the minimum completeness criteria (KKM). Based on these results, it can be said that students have good mastery of Social Arithmetic material. Student response questionnaire data obtained a percentage of 89% which indicates a good category. Overall, Google Sites interactive learning media is effectively used in the learning process in order to increase students' understanding of Social Arithmetic material and can motivate students in the learning process.